Genetic Structure and Diversity Among Historic and Modern Populations of the Sumatran Rhinoceros (Dicerorhinus sumatrensis). (7th May 2018) - Brandt, Jessica R; van Coeverden de Groot, Peter J; Witt, Kelsey E; Engelbrektsson, Paige K; Helgen, Kristofer M; Malhi, Ripan S; Ryder, Oliver A; Roca, Alfred L
Abstract: The Sumatran rhinoceros ( Dicerorhinus sumatrensis ), once widespread across Southeast Asia, now consists of as few as 30 individuals within Sumatra and Borneo. To aid in conservation planning, we sequenced 218 bp of control region mitochondrial (mt) DNA, identifying 17 distinct mitochondrial haplotypes across modern ( N = 13) and museum ( N = 26) samples. Museum specimens from Laos and Myanmar had divergent mtDNA, consistent with the placement of western mainland rhinos into the distinct subspecies D. s. lasiotis (presumed extinct). Haplotypes from Bornean rhinos were highly diverse, but dissimilar from those of other regions, supporting the distinctiveness of the subspecies D. s. harrissoni . Rhinos from Sumatra and Peninsular Malaysia shared mtDNA haplotypes, consistent with their traditional placement into a single subspecies D. s sumatrensis . Modern samples of D. s. sumatrensis were genotyped at 18 microsatellite loci. Rhinos within Sumatra formed 2 sub-populations, likely separated by the Barisan Mountains, though with only modest genetic differentiation between them. There are so few remaining Sumatran rhinoceros that separate management strategies for subspecies or subpopulations may not be viable, while each surviving rhino pedigree is likely to retain alleles found in no other individuals. Given the low population size and low reproductive potential of Sumatran rhinos, rapid genetic erosion is inevitable, though an under-appreciated concern is the potential for fixation of harmful genetic variants. Both concerns underscore 2 overriding priorities for the species: 1) translocation of wild rhinos to ex situ facilities, and 2) collection and storage of gametes and cell lines from every surviving captive and wild individual.